Transition-Metal-Free Cross-Dehydrogenative Coupling of Triazines with 5,7-Dihydroxycoumarins - Khalymbadzha, Igor A.; Chupakhin, Oleg N.; Fatykhov, Ramil F.; Charushin, Valery N.; Schepochkin, Alexander V.; Kartsev, Victor G. (Synlett, 2016)
A new method for the direct metal-free C–H functionalization of electron-deficient triazines with fragments of naturally occurring and synthetic 5,7-dihydroxycoumarins is reported. It has been found that the reaction of 5,7-dihydroxycoumarins with triazines proceeds under mild conditions, showing a high chemo- and regioselectivity.
Keywords: C–H arylation; dehydrogenative coupling; triazines; halogen-free metal-free reaction